Training motivations tests in Italian national futsal 5x5 b1 (blind sport) team - Popenko, K. S.; Makhov, A. S.; Zavalishina, S. Yu.; Medvedev, I. N. (Theory and Practice of Physical Culture, 2019)
Training motivations of the leading national Paralympians are known to be critical for the competitive success. Objective of the study was to test training motivations in the Italian national futsal 5x5 B1 (blind sport) team. The study found the motivations of the sample being dominated and driven by the individual ambitions (to qualify for the national team; compete in the top-ranking events; enjoy the public appreciation of successes; win titles in the national, European, World cups and Paralympic Games; and win a broad popularity with the titles); plus responsibility to the team for the collective success (appreciation of the individual contribution in the successful teamwork; pleasure from the training process and its every element; appreciation from the coaches etc.). Rated relatively low were the personality motivations and attitudes of the close surrounding. The study data and analysis may be beneficial for the futsal 5x5 B1 teams training system designers in their efforts to mobilize the individual resource of every team member and balance the competitive performance. Coaches are recommended giving a due priority to focused individualized efforts to foster and maintain individual motivations for the training process.